Implementation of Retail Selling Price Tariff Policy in Order to Increase Cigarette Excise Revenue at Kppbc Pasar Baru North Jakarta in 2022 - Sianturi, King Depa; Abubakar, Ibrahim (Moneta : Journal of Economics and Finance, 2023)
This research aims to analyze the implementation of the Retail Selling Price Tariff Policy in Increasing Excise Revenues and to determine the obstacles and efforts made to overcome the obstacles faced in implementing the Retail Selling Price Tariff Policy. The research was conducted at KPPBC TMP C Pasar Baru, North Jakarta using a qualitative approach and the data obtained was the result of interviews with informants and documentation. The results of the research can be concluded that the Implementation of the Retail Selling Price Tariff Policy has been running optimally in increasing excise revenue, which can be proven by the large value of Realization of Excise Revenue in the Implementation of the Retail Selling Price Tariff Policy. In its implementation, there are obstacles faced in the form of technical obstacles from internal and external parties. To overcome the obstacles that occur, preventative efforts are made by providing information and direction to Taxpayers and the Public to fulfill and comply with the provisions that have been given to minimize misunderstanding of the objectives of the Tariff Policy in its implementation.